A group concept mapping study of stakeholder perspectives on digital therapeutics economic value drivers - Yoann Sapanel; L. Martin Cloutier; Gabriel Tremblay; Anh Bourcet; Florian Koerber; David Lariviere; Xavier Tadeo; Dean Ho (npj Digital Medicine)
Abstract Digital therapeutics (DTx), software as a medical device, present a promising avenue for addressing the increasing burden of a range of conditions, yet their widespread implementation remains contingent upon demonstrating economic value—an understudied domain in current literature. Using a Group Concept Mapping approach, this study synthesized perspectives from healthcare professionals, researchers, industry, and public sector representatives to understand factors perceived to influence DTx economic value throughout its lifecycle. Analysis revealed 59 factors organized into eight clusters. Stakeholders consistently identified DTx Impact on Patient Outcomes and DTx Implementation as the most influential clusters affecting economic value. However, DTx Associated Costs and DTx Monetization Models clusters were reported as not receiving sufficient consideration throughout the DTx development lifecycle, particularly among researchers. Consequently, a conceptual framework of priority clusters and factors driving DTx economic value is proposed.